PENGEMBANGAN BAHAN AJAR KOMIK SEBAGAI MEDIA UNTUK MEREMDIASI MISKONSEPSI PADA MATERI HUKUM ARCHIMEDES DI SMP - Winanda, Nita; Maria S, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to develop comic teaching materials that are used as a medium to remediate students 'misconceptions in Archimedes' legal material in junior high school. The form of research conducted is research and development (R & D). Comic teaching materials are developed based on students 'misconceptions on Archimedes' legal material from some previous FKIP UNTAN physics education study programs. The sample in this study amounted to 99 students, namely from the eighth grade students of Pontianak City State Middle School. Comic teaching materials can be used to provide alternative teaching materials for teachers and students, based on the results of validation with the Aiken index of 1 level of validity seen in the validity of media theory, and language. Media validity is categorized as high (0.78), the validity of the theory is categorized as high (0.72) and the validity of the language is categorized as high (0.79) and the response data of students goes into the high category (85.02%). This study can be used by teachers in reducing student misconceptions in Archimedes law material, understanding the concept of learning and as an alternative teaching material for teachers and students.Keywords: teaching materials, comics, misconceptions, Archimedes law.